Unpacking the Empowerment Impact of Zakat Microcapital Programs: The Role of Entrepreneurial Character - Khatimah, Husnul; Ayuniyyah, Qurroh; Pasaribu, Popy Novita; Nurhayati, Immas (PT. Riset Press International, 2026)
This study examines the role of entrepreneurial character in shaping the economic empowerment of mentees participating in productive zakat programs. While many empowerment initiatives focus primarily on financial assistance, recent development literature emphasizes the importance of behavioral transformation in achieving sustainable economic outcomes. This research aims to empirically test whether entrepreneurial character functions as a key mechanism linking economic assistance to empowerment within the context of Islamic social finance. The study employs a quantitative explanatory design using cross-sectional survey data collected from 365 mentees participating in productive zakat programs administered by the National Zakat Agency of Indonesia (BAZNAS). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationship between entrepreneurial character and economic empowerment. The results reveal a strong and statistically significant positive effect of entrepreneurial character on economic empowerment (β = 0.763, p < 0.001). The model demonstrates substantial explanatory power (R² = 0.582) and strong predictive relevance, indicating that behavioral attributes such as persistence, opportunity orientation, and proactive action play a crucial role in sustaining economic independence among beneficiaries. These findings reinforce the behavioral empowerment perspective, suggesting that empowerment outcomes depend not only on access to capital but also on the development of internal capacities. The study contributes to the integration of entrepreneurship theory and Islamic social finance by demonstrating that productive zakat programs can serve as institutional mechanisms to cultivate entrepreneurial agency among beneficiaries. Practically, the findings highlight the importance of mentoring and character development in designing effective zakat-based empowerment programs.